THE INFLUENCE OF HUMAN RELATIONS AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE WITH ORGANIZATIONAL COMMITMENT AS A MODERATING VARIABLE AT PT. EVERBRIGHT MEDAN - Asmaul Husna; Geby Citra Ananda; Iskandar Muda (CV. Radja Publika, 2025)
This study aims to analyze the effect of human relations and work environment on employee performance at PT. Everbright Medan, as well as to examine the role of organizational commitment as a moderating variable. Data were collected from 215 employee respondents and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that human relations have a positive and significant effect on employee performance, while the work environment has a negative but significant effect. Organizational commitment also shows a positive and significant impact on employee performance. However, the role of organizational commitment as a moderating variable is not significant in strengthening or weakening the effect of human relations and work environment on employee performance. These findings emphasize the importance of harmonious interpersonal relationships, a conducive work environment, and strengthening organizational commitment to enhance employee performance. The results are expected to serve as a basis for the company in designing more effective human resource management strategies.